1990
DOI: 10.1530/acta.0.1220409
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrinological effects of ketoconazole in rats

Abstract: The effect of ketoconazole on steroid synthesis was studied in intact (sham-operated) and castrated male and ovariectomized female rats. Rats were given 25 mg/kg ketoconazole twice a day im for 5 days. The influence of ketoconazole was also investigated on hormone release altered by GnRH, estradiol and haloperidol. The following hormones were measured: serum LH, PRL, testosterone, corticosterone, 17-OH-progesterone, estradiol, and dopamine content of the tubero-infundibular area. Ketoconazole treatment resulte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…This could be a plausible explanation for the decline in serum testosterone level encountered in animal species used in the present study. Similar findings have been reported by other investigators [21]. Furthermore, it was claimed that the drug displaces testosterone from its binding globulin to allow for its rapid metabolism [22].…”
Section: Discussionsupporting
confidence: 79%
“…This could be a plausible explanation for the decline in serum testosterone level encountered in animal species used in the present study. Similar findings have been reported by other investigators [21]. Furthermore, it was claimed that the drug displaces testosterone from its binding globulin to allow for its rapid metabolism [22].…”
Section: Discussionsupporting
confidence: 79%
“…In the rat brain and in glial tumour cells, the involvement of P450 C17 in the formation of DHEA is still a matter of debate (Prasad et al 1994;Cascio et al 1998Cascio et al , 2000. Here, we show that ketoconazole, a P450 C17 inhibitor (Irsy and Koranyi 1990) reduced in a concentration-dependent manner the biosynthesis of 17OH-D 5 P, 17OH-P, DHEA and D 4 . These Fig.…”
Section: Anatomical Localization Of P450 C17mentioning
confidence: 63%
“…1998, 2000). Here, we show that ketoconazole, a P450 C17 inhibitor (Irsy and Koranyi 1990) reduced in a concentration‐dependent manner the biosynthesis of 17OH‐Δ 5 P, 17OH‐P, DHEA and Δ 4 . These results indicate that the P450 C17 ‐immunoreactive material detected in the frog brain and pituitary actually corresponds to an active form of the enzyme, that possesses both 17α‐hydroxylase and C17, 20‐lyase activities.…”
Section: Discussionmentioning
confidence: 73%
“…This study also showed that ketoconazole had no effect on baseline levels of cortisol in humans. Furthermore, ketoconazole has been found to have no effect on plasma corticosterone in ad libitum fed rats (Irsy and Koranyi 1990). In a recent study of the effects of ketoconazole on i.v.…”
Section: Discussionmentioning
confidence: 99%